Kertas kerja 3rd. congress of european microbiologists " microbes and maninterdepence and future challenges" 27 Jun - 03 Julai 2009 di Goteborg, Sweden - Kirnpal Kaur, Banga Singh (Pusat Pengajian Sains Perubatan, 2009)
Background: The Work:t Health Organization are emphasizing that the development of vaccines for Shigella is a priority. Despite many studies have been carried out on this pathogenic bacterium, but to date no vaccines are commercially available for the pubic health purposes. Apyrase is an ATP"iphosphohydrolase enzyme coded by the virulence plasmid-encoded phoN2 (spy) gene which have been suggested to be involved in proper unipolar lcsA localization and for efficient intercellular spread in Shigella. Objective: The aim of this study was to develop an apy mutant of Shigella flexneri by insertional inactivation using a kanamycin resistant gene cassette. Methods: The wild apy gene of Shigella ffexneri 2a (738 bp) was PCR amplified and the amplified gene was cloned into pTZ57R. A unique Hpa1 was identified in apy gene and a kanamycin resistant gene cassette (aphA) was inserted at the Hpa1 site of apy gene. The mutated construct (apy:aphA) was then subcloned into pWM91conjugative suicidal vector and the constructed plasmid was verifted by DNA sequencing. The mutated construct was then introduced into wild Shigella flexneri 2a by conjugation with E. coli. After undergoing homologous recombination, the wild apy gene was deleted from the construct. Results: The apy gene was successfully cloned and mutated using a kanamycin resistant gene cassette. The construct was successfully transfonned into Shigella flexneri 2a and the wild apy gene has been successfully deleted from the constructed strain. Discussion and conclusion: The mutation of apy gene is a novel approach towards the development of a potential live attenuated vaccine for Shigella; as apy gene is a potential virulence gene candidate. Further studies are in progress to evaluate the efficiency of this vaccine candidate.